2016
DOI: 10.1021/jacs.6b11022
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Charge Transfer and Ion Pairing inN,N-Diaryl Dihydrophenazine Photoredox Catalysts for Efficient Organocatalyzed Atom Transfer Radical Polymerization

Abstract: Photoexcited intramolecular charge transfer (CT) states in N,N-diaryl dihydrophenazine photoredox catalysts are accessed through catalyst design and investigated through combined experimental studies and density functional theory (DFT) calculations. These CT states are reminiscent of the metal to ligand charge transfer (MLCT) states of ruthenium and iridium polypyridyl complexes. For cases where the polar CT state is the lowest energy excited state, we observe its population through significant solvatochromic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
194
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 216 publications
(209 citation statements)
references
References 70 publications
13
194
0
Order By: Relevance
“…17 In the case of PC 4, in typical batch reactions Đ of 1.25–1.17 and I * of ∼100% were reported. 24 A summary of key photophysical and redox properties of these PCs can be found in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…17 In the case of PC 4, in typical batch reactions Đ of 1.25–1.17 and I * of ∼100% were reported. 24 A summary of key photophysical and redox properties of these PCs can be found in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] This technique provides the capability to synthesize well-defined functional polymers with a wide range of monomer types under mild conditions. [8][9][10][11][12][13][14][15][16][17][18] In O-ATRP systems, the organic photoredox catalysts (PCs) could completely replace transition metal catalysts. The high cost of post purification makes this technique losing competitiveness in terms of industrial application.…”
Section: Introductionmentioning
confidence: 99%
“…To address this challenge, we have introduced visible light organic PCs including perylene, [19a] N,N -diaryl dihydrophenazines, [19b, 23] and N -aryl phenoxazines [24] as organic PCs to mediate O-ATRP via an oxidative quenching pathway. [25] Dihydrophenazine and phenoxazine contain electron rich chromophore motifs that form rather stable radical cations upon oxidation and enable them to be strong excited state reductants.…”
mentioning
confidence: 99%
“…[8b, 9a] Recently, we reported that the lowest energy excited state of dihydrophenazine 3 is also CT in nature. [23] Specifically, intramolecular CT occurs from the electron rich phenazine core (donor) to one of the 2-naphthyl N -substituents (acceptor). Here we show that phenoxazine PC 4 similarly undergoes photoinduced intramolecular CT, as evidenced by a significant solvatochromic effect in the emission (Figure 2A).…”
mentioning
confidence: 99%